Diversity of board of directors and environmental social governance: evidence from Malaysian listed companies / Roshidah Safeei ... [et al.] - Safeei, Roshidah; Mad, Salina; Sukar, Muhamad Ashaari; Tuan Azam, Syed Khusairi; Mohamed Azhari, Muhammad Iqbal (2019)
In globally, there is increasing demand for non-financial accounting information need to be disclosed to the stakeholders. The corporate social responsibility disclosure is a one initiative in encouraging voluntary disclosure non-financial information. Meanwhile, recently environmental, social and governance (ESG) was introduced in improving the voluntary disclosure the non-monetary information to the stakeholders. The ESG has cover a broad area which can broke down into five categories: environment, workplace, community, marketplace and governance. The Environmental, Social and Governance (ESG) have become more significant in decision making of businesses in a few years ago. Bursa Malaysia has issued second edition of sustainability report guide 2018 in order to provide guidance on how to embed sustainability in business organizations (Bursa Malaysia, 2018). The businesses should identify, evaluate and manage their risks and opportunities wisely and how they can use sustainability to add value in their businesses (Bursa Malaysia, 2018). Besides that, nowadays, regulators always find a way to improve financial reporting to satisfy the needs and protect stakeholders’ interest especially investors and society. Thus, the Securities Commission of Malaysia (SC) have issued the new Malaysian Code on Corporate Governance (MCCG 2017) on 26 April 2017. This sets out best practices to strengthen corporate culture pillared on accountability and transparency (MCGG, 2017). The new MCGG 2017 is hoped that can help build an environment of trust, transparency and accountability for fostering long-term investment, financial stability and business integrity (MCGG 2017). This new code of MCCG 2017 should enhance the financial accounting reporting as well as sustainability statement. Hence, this paper will examine the relationship between diversity of board of directors and environment, social and governance disclosure in Malaysian Listed Companies.